EXPLORATION OF ETHNOVETERINARY MEDICINE FOR CATTLE’S LUMPY SKIN DISEASE IN INDONESIA: NARRATIVE REVIEW - CHOLISOH, ZAKKY; NURINNAFI’A, AHDA M. U.; SURANTO; WIKANTYASNING, ERINDYAH R. (International Journal of Applied Pharmaceutics, 2024)
Objective: Lumpy Skin Disease (LSD) is a condition characterized by the development of nodules on the skin of affected cattle. Typically, it impacts bovine animals such as cattle and buffalo. Ethnoveterinary medicine focuses on the application of traditional medicine to animals. The efficacy of traditional medicine in addressing the symptoms of lumpy skin condition was established through empirical research. Farmers can utilize medicinal plants from traditional medicine to treat bovine LSD. The primary objective of LSD treatment in cattle is to address the clinical symptoms. The objective of this study was to examine the use of LSD treatment in indigenous medicine in Indonesia. Methods: A review was conducted primarily targeting traditional medicines that have gained interest as potential treatments for cattle infected with Lumpy Skin Disease Virus (LSDV). Government authorities have specifically advised some precautions, while national mass media has raised awareness about further measures. Results: The screening result indicates that there are 9 plant species which can be used in the traditional treatment of cattle to cure LSD e. g. Nicotiana tabacum, Acorus calamus, Allium sativum, Annona muricata, Piper betle, Zingiber officinale, Curcuma xanthorrhiza, Kaempferia galanga, and Curcuma domestica, which have antimicrobial, anti-inflammatory, antioxidant, analgesic, immunostimulant, antidepressant, wound healing, and insect/larvae repellant. This research aims to contribute to the advancement of LSD treatment using conventional herbal remedies. Conclusion: Evidence from the study revealed the significance of said plants against LSDV, especially in Indonesia.